Thinking through transition : liberal democracy, authoritarian pasts, and intellectual history in East Central Europe after 1989 - Kopeček, Michal 1974- HerausgeberIn; Wciślik, Piotr HerausgeberIn (Central European University Press, 2015)
"The book intends to be the first collective monograph of the post-1989 history of political and social thought of Central, Eastern and Southeastern Europe. The project emerges from a deep conviction that the period of political transitions in the region, whether accomplished, aborted or abhorred, can and needs to be treated as a chapter in the intellectual history of political thought. Adopting the perspective of intellectual history, but inviting multidisciplinary expertise, the book aims to contribute to a more complex reflection on the post-socialist 'transition period' in East Central Europe and its historicization. While necessarily lacking comprehensiveness, it has a remarkable exploratory value for the future challenges in the field. The volume raises some of the most pressing problems of intellectual history of the period as addressed by the current scholarship, clustered into several major themes"--Provided by publisher